Physiological effects of growth stimulants on yield and quality of okra (Abelmoschus esculentus L.) - Vishnu K S (Department of Plant Physiology, College of Horticulture, 2017)
Okra or Bhindi (Abelmoschus esculentus L.) is one of the most popular summer vegetable crop grown widely in Kerala. It accounts for 65 % of the fresh vegetables exported from the country. However, the productivity of the crop is low in the state. The low fertility status of the soil due to heavy rains may be a major reason. Currently, for sustainable increase in productivity soil test based nutrient management practices are recommended. Another approach is the use of environment friendly growth stimulants, which have beneficial effects on plants. Hence, the present study was carried out to understand the influence of growth stimulants on growth, yield and quality attributes of okra variety Arka Anamika under standard package of practices (POP) recommended by KAU and also soil test based nutrient management system. The experiment was laid out in Randomized block design with 15 treatments and three replications at Central nursery, College of Horticulture, Vellanikkara. The crop was raised as per standard POP recommendations of KAU and also under soil test based nutrient management system. Experiments consisted of 15 treatments viz., standard POP, KAU (T1) as control, soil test based modified nutrient management (T2), T1 + humic acid spray @ 0.2 % (T3), T1 + potassium silicate spray @ 0.3 % (T4), T1 + cytozyme spray @ 0.2 % (T5), T1 + putrescine spray @ 50 ppm (T6), T2 + humic acid spray @ 0.2 % (T7), T2 + potassium silicate spray @ 0.3 % (T8), T2 + cytozyme spray @ 0.2 % (T9), T2 + putrescine spray @50 ppm (T10), 50 % T1 + humic acid spray @ 0.2 % (T11), 50 % T1 + potassium silicate spray @ 0.3 % (T12), 50 % T1 + cytozyme spray @ 0.2 % (T13), 50 % T1 + putrescine spray @ 50 ppm (T14) and T1 + water spray (T15). Foliar application of growth stimulants was given at 15, 30 and 45 DAS. Morphological, physiological and biochemical parameters were recorded at 25 and 50 DAS and the yield and fruit quality characters were recorded at the time of harvest. The use of growth stimulants such as humic acid, cytozyme and potassium silicate with soil test based nutrient management system improved the morphological parameters like plant height, leaf area, the number of leaves per plant etc. than control. Plants which received potassium silicate, putrescine and humic acid as foliar spray recorded higher total chlorophyll content and IAA content. Comparison of photosynthetic rate, transpiration rate and stomatal conductance of crop at two different growth stages revealed that growth stimulants such as humic acid, cytozyme and potassium silicate along with soil test based nutrient management showed a significant improvement over control. A similar pattern of the effectiveness of growth stimulants was observed in the case of fruit yield and quality characters such as crude fiber content, ascorbic acid content, mucilage content and total protein content. Comparison of POP, soil test based application of fertilizers and 50 per cent POP showed that soil test based nutrient management gave significantly higher yield as compared to the other treatments including control. The response of the stimulants was also higher for soil test based nutrient management treatments. Growth stimulants with soil test based nutrient management applied plots recorded 12 to 23 per cent higher fruit yield over control followed by standard POP with growth stimulants which recorded an improvement of 5 to 9 per cent over control. Reduction in fruit yield of 3 to 6 per cent was recorded with 50 per cent standard POP over control. Among the four growth stimulants used, humic acid performed better followed by cytozyme and potassium silicate. These growth stimulants may have enhanced the nutrient use efficiency of the plants which further improved the photosynthesis, plant growth and development. The result of the present study indicated that growth stimulants can be recommended along with soil test based nutrient management for enhancing crop growth, fruit quality and yield of okra.